(untitled) (Politeja, 2022)
FEATURES OF THE POLITICAL LEADERSHIP MODEL IN MODERN RUSSIA Reflection on political leadership is very important in the modern world. This is also relevant in the context of the political leadership in contemporary Russia, especially if we take into account a number of conditions affecting it. The aim of the article will be to trace the determinants that directly and indirectly affect the perception and functioning of political leadership in Russia, taking into account not only the issue of systemic change taking place in a specific socio-political and economic reality. Another element that will allow a closer look at the Russian model of political leadership will also be the political culture, the tradition of power and historical experiences. The third aspect, in a way complementing the spectrum of analysis of the leadership phenomenon in the Russian reality, will oscillate around the functions and tasks of the political leader of the Russian Federation, especially in the face of the challenges of the 21st century.